Training material on sheeppox and goatpox (SGP) prevention and control for pastoralists/farmers - Berhanu, Dagim; Lemma, Mamusha; Gizaw, Solomon; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2023)
Small ruminants are the main source of livelihood for millions of smallholder farmers/pastoralists in Ethiopia. Production diseases are among the major constraints to small ruminant production. Sheeppox and goatpox (SGP) is one of the diseases that affect sheep and goats production having huge economic implications. Good management plays a significant role in prevention and control of the disease. However, smallholder pastoralists/farmers have limited awareness and knowledge on the natural history of the disease and the prevention measures. Raising their awareness and knowledge through community based experiential training can help reduce disease incidence resulting in decreased economic losses.